Large Linear Magnetoresistance and Evidence of Degeneracy Lifting of Valence Bands in Rhombohedral Phase of Topological Crystalline Insulator SnTe. Issue 4 (7th January 2022) - Baral, Sonali; Dasoundhi, Mukesh Kumar; Rajput, Indu; Kumar, Devendra; Lakhani, Archana
Abstract : A comprehensive magnetotransport study on a p‐type single crystal of SnTe topological crystalline insulator is reported, across the cubic‐to‐rhombohedral ( R3m ) transition at T s ≈64 K. SnTe exhibits a large unsaturated linear magnetoresistance (LMR) reaching a value of 42% at 5 K and 8 T for (100) plane. LMR is found to have a direct dependence on the mobility and a detailed analysis shows that it follows the classical Parish‐Littlewood model of conductivity fluctuations arising from macroscopic inhomogeneities of tellurium interstitial atoms. Profound SdH oscillations having a π Berry phase are observed in the rhombohedral ( R3m ) phase having significantly lower carrier density ≈5.32 × 10 11 cm −2 at 2 K, which provides direct evidence of protected topological surface states in the R3m phase. The Hall conductivity shows a transformation from one band to two‐band behavior across the structural transition, thus providing an experimental evidence for the degeneracy lifting of bulk valence bands below the cubic symmetry breaking point which is consistent with recent band structure calculations. The overall results indicate that magnetotransport studies can distinctly probe the surface and bulk sensitive properties of SnTe, and can also track the band‐splitting of degenerate bands across the cubic‐to‐rhombohedral ( R3m ) transition. Abstract : This work reports the observation of large linear magnetoresistance in SnTe single crystal and presence of surface states in the rhombohedral phase. The Hall resistivity shows a transformation from one‐band to two‐band behavior across the structural transition providing an experimental evidence for the degeneracy lifting of bulk valence bands below the cubic symmetry breaking point as per recent theoretical predictions.